Genetic information supports a causal relationship between trace elements, inflammatory proteins, and COPD: evidence from a Mendelian randomization analysis - Cao, Zhenghua; Zhao, Shengkun; Wu, Tong; Sun, Feng; Ding, Huan; Hu, Shaodan; Shi, Li (Frontiers in Nutrition, 2024)
Objective Dietary factors and nutritional status may be among the risk factors for Chronic Obstructive Pulmonary Disease (COPD). There exists a certain correlation between trace elements and COPD. Through Mendelian Randomization (MR) analysis, we investigated the causal relationships between trace elements, inflammatory proteins, and COPD. Methods We employed MR, multivariable MR (MVMR), and two-step MR (TSMR) approaches to assess the causal links between 15 trace elements and COPD, with 91 inflammatory proteins serving as mediators to further elucidate the tripartite causal relationships. Results Trace elements such as Folate (OR = 1.293, 95%CI 1.027–1.628; p = 0.029), Vitamin D (OR = 1.331, 95%CI 1.071–1.654; p = 0.010), Vitamin B12 (OR = 1.424, 95%CI 1.108–1.828; p = 0.006), and Iron (OR = 0.741, 95%CI 0.580–0.946; p = 0.016) demonstrated causal relationships with COPD. No causal relationship was observed in reverse MR. After adjusting for BMI, Folate (OR = 1.633, 95%CI 1.098–2.429; p = 0.015), Iron (OR = 0.507, 95%CI 0.31–0.778; p = 0.001), and Vitamin D (OR = 1.511, 95%CI 1.029–2.217; p = 0.034) were identified as independent risk factors for COPD, whereas Vitamin B12 (OR = 1.118, 95%CI 0.751–1.666; p = 0.581) was not. Mediation analysis indicated that CDCP1 (5.76%) may play a mediating role between Iron and COPD. Conclusion Trace elements such as Folate, Vitamin D, Vitamin B12, and Iron have causal relationships with COPD. After BMI adjustment, Folate, Vitamin D, and Iron emerge as independent risk factors. Furthermore, the inflammatory protein CDCP1 may partially mediate the causal relationship between Iron and COPD, offering a scientific basis for dietary recommendations that could benefit COPD patients. The supplementation of trace elements may be advantageous for individuals suffering from COPD.